2013
DOI: 10.2337/db12-1045
|View full text |Cite
|
Sign up to set email alerts
|

The Type 2 Diabetes–Associated Gene Ide Is Required for Insulin Secretion and Suppression of α-Synuclein Levels in β-Cells

Abstract: Genome-wide association studies have identified several type 2 diabetes (T2D) risk loci linked to impaired β-cell function. The identity and function of the causal genes in these susceptibility loci remain, however, elusive. The HHEX/IDE T2D locus is associated with decreased insulin secretion in response to oral glucose stimulation in humans. Here we have assessed β-cell function in Ide knockout (KO) mice. We find that glucose-stimulated insulin secretion (GSIS) is decreased in Ide KO mice due to impaired rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
113
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(141 citation statements)
references
References 43 publications
23
113
1
4
Order By: Relevance
“…Also peptides structurally and physiologically unrelated, such as IAPP and the amyloidogenic determinant of the prion protein (PrP), can cross-react into morphologically distinct amyloid aggregates (46) and amyloid-β fibers can seed aS amyloid formation (47). aS is present in the pancreas (33), its levels are inversely correlated with that of IDE (31), and IDE inhibits aS amyloid formation in vitro (34,35). Despite these facts, putative cross-talk between aS and processed and/or unprocessed IAPP has not been addressed previously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also peptides structurally and physiologically unrelated, such as IAPP and the amyloidogenic determinant of the prion protein (PrP), can cross-react into morphologically distinct amyloid aggregates (46) and amyloid-β fibers can seed aS amyloid formation (47). aS is present in the pancreas (33), its levels are inversely correlated with that of IDE (31), and IDE inhibits aS amyloid formation in vitro (34,35). Despite these facts, putative cross-talk between aS and processed and/or unprocessed IAPP has not been addressed previously.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin-degrading enzyme (IDE) is a conserved metallopeptidase that can degrade insulin and a variety of other small peptides including IAPP in the pancreas (27,28). Genome-wide association studies have linked IDE to T2D (29,30) and Ide mutant mice were found to have impaired glucose-stimulated insulin secretion as well as increased levels of IAPP, insulin, and, surprisingly, aS in pancreatic islets (31,32). Here, aS may be associated with insulin biogenesis and exocytic release, as it was found to localize with insulin-secretory granules in pancreatic β-cells (33).…”
mentioning
confidence: 99%
“…The Ide gene encodes a multifunctional protein implicated in proteasome activity and protein degradation [80]. Beta cells of Ide knockout mice exhibited decreased glucose-stimulated insulin secretion, together with reduced microtubule content and autophagic flux [80].…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have demonstrated an association between Zn metallopeptidase IDE (insulin-degrading enzyme) and type-2 diabetes [12,13] . In other studies, two groups of researchers have found that IDE mutant mice have elevated level of -synuclein in pancreatic islets [9,14] . IDE is a conserved metallopeptidase that can degrade in the pancreas insulin and a variety of other small peptides including IAPP [15,16] .…”
Section: Short Communicationmentioning
confidence: 99%
“…The process of islet amyloid formation from amylin or islet amyloid polypeptide (IAPP, 37 residues, natively unfolded polypeptide) [5] causes pancreatic β-cell dysfunction, cell death, and development of diabetes. Another amyloidogenic protein, -synuclein (140 amino acids) [6,7] is expressed in several organs, including pancreatic islet b-cells where it modulates insulin secretion [8,9] .…”
Section: Short Communicationmentioning
confidence: 99%